Implementasi Undang-Undang Nomor 2 Tahun 2004 Tentang Penyelesaian Perselisihan Hubungan Industrial dalam Hal Penyelesaian Pemenuhan Hak Pekerja Wanita - Maudina, Friska; Nurdin, Maharani (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of writing this journal is to find out what women's rights are, and what companies should provide to fulfill the rights of women workers, and besides that to find out how the role of Law Number 2 of 2004 concerning industrial dispute resolution in resolving disputes over women's rights carried out by companies through the mechanism contained in Law Number 2 of 2004, specifically by way of Bipatrit settlement. The writing method used is the normative juridical method (statute approach) because in this writing it examines several statutory regulations, especially the law regarding the settlement of industrial relations disputes. then the approach taken is a statutory approach. Based on the results of the presentation of the material that has been written, it can be seen that the fulfillment of the rights of women workers has not been fully fulfilled, there are still many companies that do something about fulfilling the rights of women workers, it is not uncommon for women to even take leave on the first day and secondly when menstruation is subject to wage deductions, this is contrary to the Labor Law, in the case of not fulfilling the rights of female workers, female workers can sue the company to ask for their rights to be fulfilled, an easy settlement is done first before going further can be done by bipatrit, in this way women workers can claim to get their rights as explained in the Manpower Act.